Effect of MBOAT7 variant on hepatitis B and C infections in Moroccan patients - Ezzikouri, Sayeh; Elfihry, Raouia; Chihab, Hajar; Elmessaoudi-Idrissi, Mohcine; Zaidane, Imane; Jadid, Fatima Zahra; Karami, Adnane; Tahiri, Mohamed; Elhabazi, Abdellah; Kabine, Mostafa; Chair, Mohammed; Pineau, Pascal; et al. (Scientific reports, 2018)
The outcomes of HBV and HCV infections are associated both with viral and host genetic factors. Here, we explore the role of a genetic variation located in membrane-bound O-acyltransferase domain-containing protein 7 ( MBOAT7) gene on spontaneous clearance of HBV and HCV infections and on liver fibrosis. We genotyped MBOAT7 rs641738 polymorphism in 971 consecutive Moroccan subjects, including 288 patients with chronic hepatitis C (CHC), 98 cases with spontaneous clearance of HCV, 268 patients with chronic hepatitis B (CHB), 126 spontaneously cleared HBV infections and 191 healthy controls. MBOAT7 rs641738 variant is not associated with spontaneous clearance of HBV (OR = 0.67, 95% CI: 0.39–1.14; p = 0.131) and HCV infections (OR = 1.33, 95% CI: 0.79–2.23; p = 0.278). Furthermore, multivariable logistic regression analysis adjusted for biologically relevant covariates and potential confounders associated with the risk of liver disease progression revealed that MBOAT7 rs641738 is not associated either with fibrosis progression in CHC group (OR = 1.12; 95% CI: 0.55–2.28; p = 0.761) or with chronic progressive state in CHB patients (OR = 0.81; 95% CI: 0.41–1.61; p = 0.547). We conclude that the variant MBOAT7 rs641738 genotype is not associated with spontaneous clearance of HBV and HCV infections or with the progression of liver disease in chronic hepatitis B or C in a genetic context of Mediterranean patients.